Selected Poems : E.J. Pratt. - Pratt, E. J. (Edwin John), 1882-1964; Djwa, Sandra, 1939-; Keith, W. J.; Pollock, Zailig (University of Toronto Press, 2000)
Selected Poems offers a full sampling of Pratt's poems chosen on the joint basis of representative poetic voice and intrinsic value. The poems are based on a new edition of the texts based on a collation of all published versions.